Pengaruh Latihan Passing Menggunakan Target Terhadap Akurasi Passing Pemain Ekstrakurikuler Sepakbola SMA Negeri 1 Ciniru Kabupaten Kuningan - Prinandy, Eldi Akbar; Nurdiansya, Dani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the effect of passing practice using targets on the passing accuracy of extracurricular football players of SMA Negeri 1 Ciniru. This research is a type of quasi-experimental research. The research design used in this study is pretest-posstest one group. The population in this study is all participants of SMA Negeri 1 Ciniru Football Extracurricular which totals 20 students. The sample in this study was 11 people, taken using the purposive sampling technique. The data collection technique uses a lace ball passing test consisting of a pretest and a posttest. The data analysis techniques used were using descriptive statistical analysis and t-test. The results of the analysis showed that there was a significant influence between the pre-test and post-test of passing exercises using targets on extracurricular students of SMA Negeri 1 Ciniru